Total Loss of MHC Class I is an Independent Indicator of Good Prognosis in Breast Cancer - Z Madjd; I Spendlove; IO Ellis; SE Pinder; LG Durrant (Tehran University of Medical Sciences, 2005)
Tumours may either fail to stimulate an immune response a process known as immune ignorance or they may elicit innate and/or adaptive immunity in a process known as immune editing. Major histocompatibility complex (MHC) may play a pivotal role in immune editing as they present peptides that are recognised by cytolytic T cells. In contrast if MHC antigens are down regulated to avoid T cell attack they become susceptible to NK killing. In this study a large set of samples from patients with primary operable invasive breast cancer was evaluated for the expression of MHC class I heavy and light by immunohistochemical staining of 439 breast carcinomas in a tissue microarray. Forty seven percent (206 / 439) of breast carcinomas were considered negative for HLA class I heavy chain, whereas lack of anti-β2 m-antibody staining was observed in 39% (167/424) of tumours, with only 3% of the β2 m -negative tumours expressing detectable HLA heavy chain. A correlation with patient outcome showed a direct relationship between patient survival and HLA-negative phenotype (Log rank= 0.004). A positive relationship was found between the intensity of expression of MHC class I light and heavy chains expression and histological grade of invasive tumour (P< 0.001) and Nottingham Prognostic Index (P